The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.2337/db08-1224
|View full text |Cite
|
Sign up to set email alerts
|

Small Decrements in Systemic Glucose Provoke Increases in Hypothalamic Blood Flow Prior to the Release of Counterregulatory Hormones

Abstract: OBJECTIVE-The hypothalamus is the central brain region responsible for sensing and integrating responses to changes in circulating glucose. The aim of this study was to determine the time sequence relationship between hypothalamic activation and the initiation of the counterregulatory hormonal response to small decrements in systemic glucose.RESEARCH DESIGN AND METHODS-Nine nondiabetic volunteers underwent two hyperinsulinemic clamp sessions in which pulsed arterial spin labeling was used to measure regional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
62
4
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 31 publications
4
62
4
1
Order By: Relevance
“…The thalamus acts as a relay between subcortical and cortical areas (13), and the hypothalamus is critical for fuel homeostasis and appetite control (1). Consistent with our findings, previous studies have demonstrated thalamic and hypothalamic activation under hypoglycemic conditions (14)(15)(16). The current data demonstrating oppositely directed modulation of PFC and brain reward center activation by circulating glucose support its role in stimulating executive control regions that exert inhibitory control of feeding behavior when glucose is available and promoting survival under hypoglycemic conditions by favoring instinctual motivation for food seeking and consumption when glucose is deficient.…”
Section: Discussionsupporting
confidence: 92%
“…The thalamus acts as a relay between subcortical and cortical areas (13), and the hypothalamus is critical for fuel homeostasis and appetite control (1). Consistent with our findings, previous studies have demonstrated thalamic and hypothalamic activation under hypoglycemic conditions (14)(15)(16). The current data demonstrating oppositely directed modulation of PFC and brain reward center activation by circulating glucose support its role in stimulating executive control regions that exert inhibitory control of feeding behavior when glucose is available and promoting survival under hypoglycemic conditions by favoring instinctual motivation for food seeking and consumption when glucose is deficient.…”
Section: Discussionsupporting
confidence: 92%
“…Using PET, Teves et al 1 were the first to find that hypoglycemia activated the thalamus along with the medial prefrontal cortex, right globus pallidus, the right orbital frontal cortex, the right sensory motor cortex, and the periaqueductal gray region in healthy human participants. Others have found the hypothalamus, 3 the anterior cingulate cortex, the bilateral anterior insula, ventral striatum and pituitary, and the posterior parahippocampal gyrus 4 all to show activation at some point during the creation of and recovery from experimental hypoglycemia in healthy human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Others have found the hypothalamus to be activated in response to modest hypoglycemia using functional MRI. 2,3 More recently, the dynamics of cerebral activation during the induction of and recovery from hypoglycemia was examined by Teh et al 4 who found that at different times during the experimental period, activation could be observed in various brain areas, including the thalamic pulvinar, anterior cingulate cortex, the bilateral anterior insula, ventral striatum and pituitary, and the posterior parahippocampal gyrus in healthy human subjects.…”
Section: Introductionmentioning
confidence: 99%
“…In one seminal healthy volunteer study, mild hypoglycemia was associated with medial prefrontal and anterior cingulate cortical and thalamic activation, but the effect of duration of stimulus and recovery was not examined (Teves et al, 2004). A recent study showing regional changes in cerebral perfusion during hypoglycemia using functional magnetic resonance imaging also did not examine their time course (Page et al, 2009). Water positron emission tomography (PET) measures brain regional changes in brain perfusion with excellent signal noise characteristics over short time intervals (Raichle et al, 1983), allowing repeated measures to be made.…”
Section: Introductionmentioning
confidence: 99%